Quantitative analysis of serum metabolites in a rat model of Alzheimer’s disease - Smolentsev, Anton A.; Telegina, Darya V.; Kolosova, Nataliya G.; Tsentalovich, Yuri P.; Snytnikova, Olga A. (Frontiers in Aging Neuroscience, 2025)
ObjectiveOXYS rats are a unique animal model of sporadic Alzheimer’s disease (AD) that demonstrates all the key signs of AD in humans. Studying metabolic processes in OXYS rats in comparison with control Wistar rats can contribute to understanding the mechanisms of AD development, as well as to establishing metabolomic biomarkers of AD. The main goals of the work are to establish differences in the metabolomic profiles of OXYS and Wistar rat serum at different stages of AD-like pathology (presymptomatic, early and late).MethodsNMR-based metabolomics was applied for metabolomic profiling of blood serum of OXYS and Wistar rats at the age of 20 days (presymptomatic period), 4 months (first manifestation of signs of AD) and 16 months (active development of signs).ResultsWe determined the concentrations of 55 metabolites present in rat serum. We found that age-related changes in both rat strains reflect animal maturation (20 days to 4 months) and aging (4 months to 16 months), and correspond mainly to amino acid metabolism, purine metabolism, and energy pathways. Potential AD blood biomarkers include lysine, BCAAs, alanine, ornithine, creatine, glutamine and pyruvate.ConclusionThe most significant differences between OXYS and Wistar blood metabolomes were found for 20-day-old animals, which corresponds to the preclinical period of AD development in humans. Metabolomic changes observed in the brain and blood are different and often opposite in sign. Blood serum is potentially promising fluid for AD diagnosis.